Robot ROV Underwater Berbasis Mikrokontroler - Rahman Wijaya, Muhammad Fathur; Kurniantoro, Haji Luhung; Mediaâ€™s, Ermi (Autocracy: Jurnal Otomasi, Kendali, dan Aplikasi Industri, 2016)
Underwater robot Remotely Operated Vehicle (ROV) base on microcontroller Arduino Mega 2560, monitoring underwater using Gopro Camera with Joystick ps2 as control and maneuver in underwater. Research intended to design, create, and examine The Underwater Robot Remotely Operated Vehicle (ROV) base on microcontroller Arduino Mega 2560, as monitor underwater using Gopro Camera with Joystick ps2 as control and maneuver in underwater to do an observation task underwater controlled directly by user. Research method used is research and development. Remotely Operated Vehicle (ROV) is made by main signal processor such as microcontroller Arduino Mega 2560 and controlled by Joystick ps2. Gopro Cam as a monitor to see underwater on frame ROV. Driver motor module Electronic Speed Control (ESC) is used to managing Rovâ€™s speed. The result of our research â€œRobot Remotely Operated Vehicle (ROV) Underwater sas monitor underwater base on Mikrokontroler Mega 2560â€, able to explore underwater, dive into the surface till 70 cm depth and 3,50 seconds Robot Underwater Remotely Operated Vehicle (ROV) berbasis mikrokontroler Arduino Mega 2560, sebagai memonitoring bawah air tawar menggunakan kamera gopro dengan dikontrolnya menggunakan Joystick ps2 dan dapat bermanuver di bawah air tawar. Penelitian bertujuan untuk merancang, membuat, dan menguji Robot Underwater Remotely Operated Vehicle (ROV) Berbasis Mikrokontroler Arduino Mega 2560 sebagai memonitoring bawah air tawar menggunakan kamera gopro dengan dikontrolnya menggunakan Joystick ps2 dan dapat bermanuver di bawah air tawar sehingga dapat menjalankan tugas observasi bawah air tawar dengan kendali langsung oleh pengguna. Metode penelitian yang digunakan adalah metode research and development. Robot Underwater Remotely Operated Vehicle (ROV) ini dibuat dengan sistem pengolah sinyal utama berupa mikrokontroler Arduino Mega 2560 dan dikontrol oleh Joystick ps2. Kamera Gopro sebagai monitor untuk melihat bawah air yang terdapat pada frame robot ROV. Modul driver motor Electronic Speed Control (ESC) digunakan untuk mengatur kecepatan motor Robot ROV. Dari hasil penelitian â€œRobot Remotely Operated Vehicle (ROV) Underwater sebagai Memonitor Bawah Air Tawar Berbasis Mikrokontroler Mega 2560â€, mampu menjelajahi bawah air tawar, serta dapat menyelam dari permukaan air tawar sampai ke dalaman 70 cm selama 3,50 detik.